2014
DOI: 10.14260/jemds/2014/3230
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Immediate Ppiucd Application in Bundelkhand Region

Abstract: To assess the safety, acceptability, efficacy, feasibility and complication of immediate PPIUCD insertion. METHODS: Cu T 380A was used for PPIUCD insertion immediately following delivery of placenta during caesarean section or within 48 hours following childbirth. RESULT: The study was conducted in obstetrics and gynecology department in MLB Medical College Jhansi. The total number of deliveries during the study period was 4695, among these 1941 women were eligible for PPIUCD insertion.423 women accepted PPIUC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
31
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 9 publications
13
31
2
Order By: Relevance
“…These findings are similar as results observed by Deshpande et al and Gujju et al 14,17 Present study revealed that there was higher acceptance rate among multipara (69.59%) and those who had a desire for future pregnancy after an interval of more than 2 years (75.64%) this is similar to finding reported by Deshpande et al but in contrary to study conducted by Mishra and by Gautam et al it was seen that there was a higher acceptance in primigravida. 14,18,19 This observation suggests that in present study multi gravida were more receptive to this spacing method of contraception.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…These findings are similar as results observed by Deshpande et al and Gujju et al 14,17 Present study revealed that there was higher acceptance rate among multipara (69.59%) and those who had a desire for future pregnancy after an interval of more than 2 years (75.64%) this is similar to finding reported by Deshpande et al but in contrary to study conducted by Mishra and by Gautam et al it was seen that there was a higher acceptance in primigravida. 14,18,19 This observation suggests that in present study multi gravida were more receptive to this spacing method of contraception.…”
Section: Discussionsupporting
confidence: 52%
“…Deshpande et al and Mishra have similar findings. 14,18 Our study reveals that refusal from partner/family member for PPIUCD insertion was most common (72.75%) reason for refusal followed by fear of complications (69.96%) as was found by Sonali Deshpande et al, Mishra and Gautam et al 14,18,19 This suggests that health care provider should understand the importance of couple counselling for contraception decision making. A gender-sensitive approach should be adopted for couples counselling to achieve better compliance and to met unmet need for contraception.…”
Section: Discussionmentioning
confidence: 54%
“…Such women were counselled easily and had better acceptance as reported in other studies too. 4,6,7 Higher number of Hindu patients could be related to predominance of Hindu population in our area. There was significant difference in parity in the two groups with a clustering of cases at Para2 in Group B as reported in other studies also.…”
Section: Resultsmentioning
confidence: 84%
“…Acceptance was higher in Caesarean group, similar to other studies. 4 Mean age was comparable in both groups (26.21 years in vaginal & 25.41 years in Caesarean) probably because most females coming to the hospital for delivery belong to the same age group. 5 Higher acceptance in illiterates, less educated cases and cases with low socio-economic status can be related to their willingness for contraceptive use with a fear of failure to return back.…”
Section: Resultsmentioning
confidence: 88%
“…Inadequate knowledge about contraceptive methods and incomplete or erroneous information about their use or where to procure them are the main reasons for not accepting family planning. 10 Providing quality contraception methods to women is one of the cornerstones for achieving millennium development goals of improved maternal and child health.…”
Section: Introductionmentioning
confidence: 99%